Validation of a rapid ultra‐high‐performance liquid chromatography–tandem mass spectrometry method for quantification of chlorogenic acids in roasted coffee. (10th August 2020) - Colomban, Silvia; Guercia, Elena; Navarini, Luciano
Abstract: Chlorogenic acids (CGAs) are a large class of esters formed between quinic acid and hydroxycinnamic acids. They are present in coffee as a complex mixture of positional and geometric isomers, where caffeoylquinic acids (CQAs) are the most abundant, followed by dicaffeoylquinic acids (diCQAs), feruloylquinic acids (FQAs), and p‐coumaroylquinic acids (p‐CoQAs). The aim of this work is to develop a new reliable and fast liquid chromatography–tandem mass spectrometry (LC–MS/MS) method for simultaneous identification and quantification of total amount of 11 CGAs in roasted coffee. Regarding sample preparation step, aqueous methanol and 100% aqueous ultrasonic extractions were evaluated. For the filtration Step 4, different membranes were tested, in order to fill the void of complete evaluation of extractables recovery when using different membranes, highlighting an incomplete recovery when using nylon filters. An LC/electrospray ionization (ESI)–MS/MS method was developed and validated following the European rules in terms of specificity, linearity, concentration range, limit of detection (LOD) and limit of quantification (LOQ), precision, and trueness, in order to obtain a useful quality control tool for roasted coffee. The method was applied for quantification of CGAs of a roasted coffee sample previously characterized by an interlaboratory circuit (LVU), and results were compared with the quantitation of CGAs via UHPLC‐DAD. The quantitative results were expressed as 5‐CQA equivalents, and the validation of this approach opens the way to reliable, cheap, and environmental‐friendly tools for quality control purposes.